2008
DOI: 10.1080/00207590701484827
|View full text |Cite
|
Sign up to set email alerts
|

The importance of values in predicting Turkish youth's opinions about the European Union in light of the Copenhagen Political Criteria

Abstract: The enlargement process of the European Union may be regarded as one of the most important social projects of human history in that it is trying to unite several nation-states under a "European identity." As a historically and culturally "distant" candidate, Turkey has been asked to meet a set of expectations referred to as the "Copenhagen Criteria," requiring a series of large-scale reforms to the infrastructure and superstructure of the country. Taking advantage of the unique opportunity to relate Turkish pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Attributing high importance to self-transcendence and openness-to-change values has been found to be positively correlated with tolerance towards Arabs among Israeli Jews. The reverse correlation was found for conservation values (Sagiv & Schwartz, 1995; see also Kuşdil & Şimşek, 2008). Similarly, a study of 19 European countries (based on the European Social Survey) showed that valuing self-transcendence is positively related to and valuing conservation is negatively related to support for immigration (Davidov, Meuleman, Billiet, & Schmidt, 2008).…”
Section: Direct Effects Of Values On Tolerancementioning
confidence: 79%
“…Attributing high importance to self-transcendence and openness-to-change values has been found to be positively correlated with tolerance towards Arabs among Israeli Jews. The reverse correlation was found for conservation values (Sagiv & Schwartz, 1995; see also Kuşdil & Şimşek, 2008). Similarly, a study of 19 European countries (based on the European Social Survey) showed that valuing self-transcendence is positively related to and valuing conservation is negatively related to support for immigration (Davidov, Meuleman, Billiet, & Schmidt, 2008).…”
Section: Direct Effects Of Values On Tolerancementioning
confidence: 79%
“…SDO did not significantly correlated with any type of values in the present study. However, there were several indications that nationalism correlates with values in previous studies in Turkey (Hortaçsu & Cem-Ersoy, 2005;Kuşdil & Şimşek, 2007). As for the associations between Schwartz's values and other key variables, Gürşimşek and Göregenli (2005) reported that participants with higher scores on traditionality power and conformity were seen to have higher scores on system justification.…”
Section: Discussionmentioning
confidence: 90%
“…In this historical respect, cultural, regional and religious differences and occasionally conflict have characterized Turkish-European relations. Thus, the main dimensions of differentiation between Turkey and Europe are differences with respect to EU criteria concerning economy and human rights and cultural/religious differences reflected by the history of conflict (Hortaçsu & Cem-Ersoy, 2005;Kuşdil & Şimşek, 2007). The last two decades were characterised by political and social reforms in Turkey since accession negotiations started in October, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Şen et al (2005), discourses of moral degeneration (articulated by a perceived threat to Turkey's culture and lifestyle) and nationalism (expressed by a perceived threat to the unity and integrity of the nation and the state) are the two main underlying characteristics of Euro-scepticism. Similarly, other studies show that social and personal values, such as ethno-centrism and patriotism, together with nationalism and religiosity, are the most effective predictors of young people's views on the EU (Hortaçsu and Cem-Ersoy, 2005;Kuşdil and Şimşek, 2007).…”
Section: Current State Of Turkish Youth Researchmentioning
confidence: 80%